Potentiometric studies on complexes of Cr (â…¢) and Zr (IV)with some carboxylic acids - Omar, Abdalazeem; Ali, Elmugdad (International Journal of Advanced Chemistry, 2015)
The present work, deals with the study of proton-ligand (pK) and metal-ligand (logK) of acetic acid, oxalic acid, and oxalacetic acid with Cr (â…¢) and Zr (IV) by potentiometric titration technique. The stoichiometries and stability constants of these complexes were evaluated, usingCalvin-Bjerrum pH-titration technique as adopted by Irriving and Rossotti.Graphic and algebraic methods have been employed, for determination of the stability constants, in purpose to select the most accurate and sensitive method. Furthermore, aiming to determine, the factor that effectingthe precision of those methods under investigation, and to compare the complexes of these ligands with first and second series transition elements of D-block Cr and Zr taken as an example. The obtained results were in a good agreement with each other.